VD_FINDINFO ML / 2016 / 201 vom 23. August 2016 - VD Tribunal cantonal (2016)
MAINLEVÉE PROVISOIRE, TITRE DE MAINLEVÉE, BAIL À LOYER, TRANSFERT DE BAIL | 253 CO, 263 CO, 264 CO, 82 al. 1 LP, 82 al. 2 LP, 82 LP